High-throughput satellites - Fenech, Hector (Artech House space technology and applications library., 2021)
This exciting new book discusses the motivation for the evolution of a new breed of High Throughput Satellites (HTS) that have emerged from traditional communications satellites. It explores the commercial sectors and technical context that have shaped HTS. The historical underpinnings of HTS are provided to highlight the requirements that dimension these satellites. A survey of operational GEO HTS systems is also included. Readers will understand the technical, operational and commercial context of HTS systems, as well as the performance of the current HTS system. & nbsp; This initial breed of satellites was limited to geostationary satellites, but it is quickly projecting into low earth orbit (LEO) constellations, often referred to as mega-constellations. The industrial and operational facets of LEO constellations are challenging. The characteristics of GEO and LEO systems are presented to understand the differences between the two systems. The book also explores the evolution of the current HTS payload architectures, as well as theoretical methodology is presented for the capacity estimation for both the FORWARD link and RETURN link, which can be used for preliminary HTS dimensioning and can be adapted to practical scenarios.